2015
DOI: 10.2337/dc15-1391
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of Diabetes Management via Clinical Video Telehealth

Abstract: Figure 1-Patient satisfaction survey results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Improved access to quality care and reductions in health care utilization expenses are additional benefits of telehealth technology. Three of the four telehealth cost analysis reviews demonstrated promising benefits with regard to reducing treatment costs and complications for patients living in rural areas (1316). Varied telehealth models are available as an alternative to in-person medical and educational encounters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Improved access to quality care and reductions in health care utilization expenses are additional benefits of telehealth technology. Three of the four telehealth cost analysis reviews demonstrated promising benefits with regard to reducing treatment costs and complications for patients living in rural areas (1316). Varied telehealth models are available as an alternative to in-person medical and educational encounters.…”
Section: Resultsmentioning
confidence: 99%
“…Telehealth is also used for reducing costs, time, and risks associated with traveling to a main medical center (13). A pilot quality improvement program to provide CVT pharmacotherapy clinics for patients with diabetes was implemented at the West Palm Beach Veterans Affairs Medical Center (WPBVA) from 1 October 2012 to 30 April 2013.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Philip analyses the expansion of clinical pharmacy through increased use of outpatient pharmacists for anticoagulation services (Philip et al, 2015 ). Verbosky assesses the implementation of diabetes management via telehealth, whilst Owsley evaluates telemedicine for diabetic eye screening (Owsley et al, 2015 ; Verbosky et al, 2016 ). Singh studies the implementation and benefits of a pharmacist-managed telehealth anticoagulation clinic (Singh et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%